Evaluation of photocatalytic active coatings on sintered glass tubes by methylene blue - Lekelefac, Colin Awungacha; Czermak, Peter; Herrenbauer, Michael (My University, 2013)
A comparative study between ten different photocatalytic active coatings was done. The effectiveness and photocatalytic activity of the coatings were studied by degradation experiments of methylene blue (MB) dye under UV light illumination. The reactor design consisting of sintered glass packed in a borosilicate tube placed between two planar dielectric barrier discharge lamps (Osram Planon) is reported for the first time. The coatings consisted of either titania, silica, or zinc on sintered borosilicate glass. The advantage of sol-gel in catalyst preparation was exploited to combine catalyst to act as cocatalyst. TiO[subscript 2]-P25 widely applied in suspension systems was effectively immobilized on sintered glass support with the aid of tetraethylorthosilicate (TEOS) solution which acted as support material. Results indicated that TiO[subscript 2]-P25+SiO[subscript 2], TiO[subscript 2]-P25+SiO[subscript 2]+Pt, and TiOSO[subscript 4]_30,6wt% films showed highest degradation rates close to 100% after 90 min illumination with degradation rates exceeding 50% after 30 minutes. TTIP+Pt showed lowest degradation rate.
Keywords: Photocatalytic active coatings; Methylene blue; Sintered glass